Exciton characteristics in graphene epoxide - Zhu, Xi (2014)
Exciton characteristics in graphene epoxide (GE) are investigated by density functional theory with quasi-particle corrections and many-body interactions. The nature of the exciton is influenced by epoxide content and detailed geometric configurations. Two kinds of excitons are identified in GE: Frenkel-like exciton originated from the sp2 carbon cluster and charge-transfer exciton formed by localized states involving both oxygen and carbon atoms. The unusual blue shift associated with the Frenkel-like exciton leaking is highlighted. One scaling relationship is proposed to address the power-law dependence of Frenkel-like exciton binding strength on its size. The charge-transfer exciton appears in GE samples with the high oxygen coverage. Particularly, the exciton in GE structures exhibits long lifetime by analyzing both radiative and nonradiative decay processes. This study sheds light on the potential applications of GE-based structures with attractive high quantum yield in light emission and optoelectronic technology.